CLINICAL SIGNS OF CHEMOTHERAPY-INDUCED NEUROPATHY IN CANCER PATIENTS AND PHARMACOTHERAPY CORRECTION OPTIONS - I. A. Zolotovskayaia; I. L. Davydkin; T. M. Lokshtanova; A. E. Orlov (Архивъ внутренней медицины)
The study objective was to analyze the clinical signs of chemotherapy-induced neuropathy (CIPN) in cancer patients and explore pharmacotherapy correction options using vitamin B. Materials and design. During Part 1 lasting from May to September 2017, we screened and then enrolled 219 consecutive patients (mean age of 50.4 ± 6.9 years); 105 (46.7%) of them were women undergoing chemotherapy treatment cycles at Samara Regional Oncological Clinic. Through standard-of-care neurological examination and patient responses we defined the clinical signs of polyneuropathy: its localization, primary symptoms, including sensory impairments and/or pain, and then randomized the patients into two groups: group 1 received vitamin B agents, and group 2 received no vitamin B. The patients were observed for 60 days. Results. The incidence of polyneuropathy in oncology patients receiving chemotherapy turns out to be very high. The phenotype of clinical signs and their severity and localization is probably related to the type of the drug agent used. We have proved the efficacy of the step-down therapy with vitamin B agents used to improve clinical signs of polyneuropathy.